Correlation between Serum Albumin and Fasting Blood Glucose Level in Patients with Liver Cirrhosis - Nenny Agustanti; Ali Djumhana; Siti Aminah Abdurachman; Soetodjo NMN (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Liver cirrhosis is a pathological condition describes the end-stage of liver fibrosis. On liver damage may occur impaired glucose metabolism such as insulin resistance and glucose intolerance. The correlation between chronic liver diseases with impaired glucose metabolism has been known as hepatogenous diabetes. Albumin levels were significantly affected by poorly controlled blood glucose seen from the high HbA1c. This study aims to determine correlation of serum albumin level and fasting blood glucose level in patients with liver cirrhosis.Method: This cross-sectional study was conducted in 52 patients with liver cirrhosis in Gastroentero-hepatology Clinic and Inpatients, Hasan Sadikin Hospital. The study was conducted from February to June 2013. History taking, physical examination and laboratory tests including liver function tests and fasting blood glucose were performed. Data were analyzed using Spearman rank test for the correlation.Results: There were 31 (59.6%) males and 21 (40.4%) females with mean age 53.4 ± 12.8 years. The mean serum albumin was 2.7 ± 0.5 g/dL and median fasting blood glucose was 100 (66-195) mg/dL. Etiology of liver cirrhosis was hepatitis B virus infection 28 (51.9%), hepatitis C virus infection 16 (30.8%) and non viral hepatitis B and C infection 9 (17.3%). Severity of cirrhosis scored using child turcotte pugh (CTP) which was 43 (82.7%) of CTP B and 9 (17.3%) of CTP C. There was statistically significant correlation between albumin level and fasting blood glucose with ρ = -0.630 and p 0.01.Conclusion: In patients with liver cirrhosis have low serum albumin level correlates with high fasting blood glucose. Keywords: cirrhosis, albumin, fasting blood glucose